The influence of animation video media on the interests and learning outcomes of elementary school students - Sintya Hayaturrohmah; Suwito Eko Pramono; Arief Yulianto (Inovasi Kurikulum, 2025)
This study aims to determine the effect of using animated video content on the learning outcomes and interests of SD Negeri Parebon 03 fourth-grade students. The research methodology used is a quantitative approach. In this study, student involvement and learning outcomes are the dependent variables, while animated video content is the independent variable. The sample used in this study was 28 fourth-grade students. The data collection method used was a multiple-choice learning outcome questionnaire that had been validated for validity, an interest questionnaire, and observation. Using basic linear regression tests, descriptive and inferential analysis techniques were used to analyze the data. The average score before therapy was 52. After treatment, the average score increased to 84 for descriptive statistical analysis. Examining inferential statistics of animated video content on test-based learning interest tests showed increased learning interest. At the same time, animated video content showed increased learning outcomes. In conclusion, the interest and learning outcomes of SD Negeri Palebon 03 fourth-grade students on plant breeding material were significantly influenced by animated video content. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh penggunaan konten video animasi terhadap hasil dan minat belajar siswa kelas IV SD Negeri Parebon 03. Metodologi peneltiian yang digunakan adalah pendekatan kuantitatif. Dalam penelitian ini keterlibatan siswa dan hasil belajar menjadi variabel terikat, sedangkan konten video animasi menjadi variabel bebas. Sampel yang digunakan dalam penelitian ini adalah siswa kelas IV sebanyak 28 siswa. Metode pengumpulan data yang digunakan adalah angket hasil belajar pilihan ganda yang telah tervalidasi validitas, angket minat, dan observasi. Dengan menggunakan uji regresi linier dasar, teknik analisis deskriptif dan inferensial digunakan untuk menganalisis data. Skor rata-rata sebelum terapi adalah 52, dan setelah perlakuan, skor rata-rata meningkat menjadi 84 untuk analisis statistik deskriptif. Pemeriksaan statistik inferensial konten video animasi pada tes minat belajar berbasis tes menunjukkan peningkatan terhadap minat belajar. Sedangkan konten video animasi menunjukkan peningkatan terhadap hasil belajar. Kesimpulannya, minat dan hasil belajar siswa kelas IV SD Negeri Palebon 03 terhadap materi pemuliaan tanaman dipengaruhi secara signifikan oleh konten video animasi.Kata Kunci: hasil belajar; minat belajar; video animasi